A comparative analysis of bioethical issues from view points of Religious Affairs Administration in Turkey, Roman Catholicism and Orthodox Judaism - Huseyin Guvercin, Cemal; Munir, Kerim M. (Acta Bioethica, 2017)
The arguments set forth by religious authority are important since it play a crucial role in shaping the social values of the public and influence the decision of individuals in the practice pertaining to bioethical issues. The Religious Affairs Administration (RAA) was established at the inception of the Republic of Turkey in 1924 to guide religious considerations moving out of the Ottoman caliphate to a secular bioethical framework. In this article, the bioethical views of the RAA under Islamic tradition is examined and contrasted with those influenced by the Roman Catholic and Orthodox Judaic traditions. On bioethical deliberations related to the beginning and end-of-life, all three religious traditions justify sacredness of life and that of God’s will in preservation it. Assisted reproduction techniques between spouses is considered to be appropriate, although third party involvement is explicitly forbidden. Organ transplantation is approved by all three religious traditions, except uterine transplantation. The contraceptive practices are approved under certain conditions — the views differ most on approaches to contraception and the appropriateness of methods. The RAA has judgement on cloning is to prohibit it, like Roman Catholicism and Orthodox Judaism. In other topics, cosmetic surgery and gender determination are approved only for treatment.